2002
DOI: 10.1007/s00425-002-0752-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of petal and pollen development by the plant cyclin-dependent kinase inhibitor ICK1 in transgenic Brassica plants

Abstract: The cyclin-dependent protein kinases (CDKs) have a central role in cell cycle regulation and can be inhibited by the binding of small protein CDK inhibitors. The first plant CDK inhibitor gene ICK1 was previously identified in Arabidopsis thaliana. In comparison to known animal CDK inhibitors, ICK1 protein exhibits unique structural and functional properties. The expression of ICK1 directed by the constitutive CaMV 35S promoter was shown to inhibit cell division and plant growth. The aim of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 42 publications
5
56
1
Order By: Relevance
“…This result is in apparent contradiction to previously reported KRP overexpression studies (De Veylder et al, 2001;Jasinski et al, 2002;Zhou et al, 2002;Schnittger et al, 2003) but is in agreement with the observed stimulation of the endoreduplication cycle in weak KRP2 OE plants (Verkest et al, 2005). In addition, although KRP5 overexpression does not affect overall plant size, some results reported here suggest that KRP5 can negatively influence cell proliferation.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This result is in apparent contradiction to previously reported KRP overexpression studies (De Veylder et al, 2001;Jasinski et al, 2002;Zhou et al, 2002;Schnittger et al, 2003) but is in agreement with the observed stimulation of the endoreduplication cycle in weak KRP2 OE plants (Verkest et al, 2005). In addition, although KRP5 overexpression does not affect overall plant size, some results reported here suggest that KRP5 can negatively influence cell proliferation.…”
Section: Discussioncontrasting
confidence: 73%
“…As demonstrated by their ability to inhibit CDK activity, plant KRP genes encode functional CKIs. Several reports have established that KRPs bind CDKs of the CDK A type and B type (Lui et al, 2000;De Veylder et al, 2001;Jasinski et al, 2002;Zhou et al, 2002), suggesting that they could all function at the G1/S transition and at the G2/M transition. Consistently, CDK complexes containing cyclin D or A can be inhibited by KRPs in vitro (Coelho et al, 2005), and overexpression of KRPs can restore the growth defects induced by D-type cyclin overexpression (Jasinski et al, 2002;Schnittger et al, 2003;Zhou et al, 2003).…”
mentioning
confidence: 99%
“…However, the callus with the highest expression of Zeama;KRP;1 had the lowest percentage of endoreduplicated nuclei and there was no evidence of endoreduplication in calli expressing RepA only. Overexpression of the Zeama;KRPs by themselves severely reduced growth of embryonic maize calli, as was observed in several previous studies in which CKIs were constitutively expressed , Jasinski et al, 2002, Zhou et al, 2002a, 2002b.…”
Section: Zeama;krp;1 Overexpression Can Lead To Endoreduplication In supporting
confidence: 78%
“…Because of the sequence similarity between the plant and mammalian CKIs of the Cip/Kip family, it has been inferred based on indirect evidence that the plant KRPs inhibit CDK activity through interaction with cyclin/CDK complexes (Wang et al, 1998;De Veylder et al, 2001;Jasinski et al, 2002;Zhou et al, 2002aZhou et al, , 2002bSchnittger et al, 2003).…”
Section: Zeama;krps Are Ckis That Can Affect Cyclin A/cdk and Cyclin mentioning
confidence: 99%
“…Roots were removed from 9-day seedlings and the shoot part (almost entirely leaves) was used for flow cytometric analysis as described (Zhou et al, 2002). Briefly, fresh leaf tissue from mature Arabidopsis leaves was sampled in a 60-mm petri plate containing 400 µl of solution A of the High Resolution DNA kit-Type P (Partech, Munster, Germany).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%